ISHLAB CHIQARILGAN MAHSULOT TANNARXI TO‘G‘RISIDAGI HISOBOTI - Xudaynazarova Dilnoza,; Abduahadov Samandar, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the preparation of the report on the cost of manufactured products, focusing on both theoretical and practical aspects. The study analyzes the concept  of  product  cost,  its  economic  essence,  and  its  role  in  accounting.  It  also considers the classification of production costs and the principles of including them in the cost of production. The article describes in detail the methods of calculating product cost, the stages of its formation, and the procedure for preparing cost reports. The application of the weighted average method and other costing methods is also analyzed in practice. The results of the study show that the cost of production report plays an important role in determining  financial  results,  controlling  expenses,  and  supporting  managerial decision-making in enterprises.